Measuring the effect of the anti-nerve growth factor antibodies bedinvetmab and frunevetmab on quality of life in dogs and cats with osteoarthritis using a validated health-related quality of life outcome measure: an observational real-world study - Reid, Jacqueline; Gildea, Edwina; Davies, Vinny; Thompson, Jill; Scott, Marian (Frontiers in Veterinary Science, 2024)
Background Osteoarthritis causes chronic pain, impaired joint function, decreased mobility and negatively impacts quality of life (QOL). Anti-nerve growth factor antibodies bedinvetmab for dogs and frunevetmab for cats are licensed for the alleviation of osteoarthritis pain but their QOL impact is unreported. Our aim was to determine if these therapeutics improve QOL using a validated health-related QOL measure that generates scores in four domains of QOL-energetic and enthusiastic (E/E), happy and content (H/C), active and comfortable (A/C) and calm and relaxed (C/R)-in the dog and three in the cat-vitality, comfort and emotional wellbeing (EWB). Summary scores for physical wellbeing (PWB) and emotional wellbeing (EWB) for dogs and PWB for cats are calculated from the domain scores. Methods Animals received bedinvetmab (dogs) at 0.5–1 mg/kg or frunevetmab (cats) at 1–2.8 mg/kg by subcutaneous injection on days 0, 28 and 56 and owners completed QOL assessments within 48 hours of day 0 and on days 14, 28, 56, 63 and 70 using a study-specific app. Results Assessments were completed by 75 dog and 56 cat owners. By day 14 there was a statistically significant improvement (p ≤ 0.001) in PWB, EWB and all domains except C/R (p = 0.005) in dogs and in all domains and PWB in the cat. Subsequently there was a continued improvement in all domains and summary scores (p ≤ 0.001) except for H/C in the dog and EWB in the cat, which were excluded from the statistical model. The overall improvement in all domain scores in the cat and E/E and A/C in the dog exceeded the previously reported minimum important difference scores for the QOL measure, indicating a clinically significant change. Conclusion Treatment with bedinvetmab and frunevetmab produced a significant improvement in the QOL of dogs and cats. This latest evidence for the use of these OA pain medications could be helpful in the clinical management of osteoarthritis and post-marketing clinical trials.